A review on using of both electro-osmosis and electrokinetic soil treatment methods to improve bearing capacity of soft clayey soils - Yasun, Azhar Sadiq; Mohammed Shafiqu, Qassun S.; Güler, Erol (Al-Nahrain Journal for Engineering Sciences, 2026)
An overview of electro-osmosis (EO) and electrokinetic (EK) soil treatment methods is provided in this paper, along with their impact on pile capacity, installation, and foundation shear strength after improving the geotechnical properties of weak soils, particularly soft clays. As a result of their low shear strength, high compressibility, and poor drainage characteristics, soft clayey soils pose significant challenges in civil engineering. With EO and EK, pore water and ions are moved through the soil matrix under an applied electric field, resulting in consolidation, increased shear strength, and reduced plasticity. This review explores the fundamental principles of EO and EK, including the mechanisms of water transport, ion migration, and electrochemical reactions. It examines various electrode configurations, treatment parameters, and their influence on soil improvement. Furthermore, the paper analyzes the effects of EO treatment on pile capacity, considering both the increase in soil strength and the reduction in pore water pressure during installation. The impact on pile installation methods, such as reducing driving resistance and improving grout penetration, is also discussed. Finally, the review investigates the enhancement of foundation shear strength through improved soil properties achieved by EO/EK treatment. By synthesizing existing research, this paper aims to provide a comprehensive understanding of the potential benefits and limitations of EO and EK methods for ground improvement in soft clayey soils, offering valuable insights for future research and practical applications in geotechnical engineering.